Innovative Strategies in Developing Modern Desserts and Strengthening Human Resources: A Consumer Perspective - Annabellla Putri Rengganis; Isniar Budiarti; Alya Shalma Hadiniah; Muhamad Fariz Alifananda (IJSM, 2026)
This study aims to explore how innovative strategies are applied in the development of modern dessert products from a consumer perspective, with a particular focus on the brand Bittersweet by Najla. The research focuses on product innovation, visual presentation, creative branding strategies, digital approaches, and human resources (HR) aspects that support the successful implementation of innovation. The study employed a descriptive qualitative method using semi-structured interviews with consumers who had purchased and experienced Bittersweet by Najla products. The findings reveal that consumers perceive Bittersweet by Najla as successfully delivering comprehensive innovation through a combination of unique flavors, aesthetic packaging, strong branding narratives, and services supported by well-trained HR. These innovative strategies positively impact emotional satisfaction, experiential value, and consumer loyalty to the brand. The results indicate that innovative strategies not only serve as differentiators in the competitive culinary industry but also as a means of building meaningful consumer relationships. Therefore, MSME players in the modern dessert sector are encouraged to consistently innovate and strengthen HR capacity through training, performance management, and appropriate recruitment strategies to meet the demands of a dynamic market.